FOMER CHILD SOLDIERS: PRODUCT OF ARMED CONFLICTS AND HOW THE INTERNATIONAL CRIMINAL COURT FAILS TO SEE ITS SIGNIFICANCE - Dino Panji Pananjung; Sigar Aji Poerana (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
AbstractIn armed conflicts, children are often kidnapped and forced to become child soldiers, they are also given forced indoctrination (by violence and threats) and are taught to commit crimes, such as looting and murder. Disobeyed children and those who try to escape will be punished in the form of torture or even being executed in front of other children's soldiers as a lesson so others will not follow their step. When they did not serve the armed forces anymore or they grew up and no longer held child status, they were given the title of